Penggunaan Game Edukasi Kahoot! Untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Teknologi Dasar Otomotif Kelas X TKRO di SMK Negeri 1 Sumatera Barat - Nursyafti, Yolana; Sukmawati, Murni (Universitas Negeri Padang, 2022)
This study aims to see the improvement of student learning outcomes in the application of the educational game Kahoot! on the subject of Basic Automotive Technology class X TKRO at SMK Negeri 1 West Sumatra. This study uses a type of quasi-experimental research. The number of samples in each experimental and control group was 36 students. Normality, homogeneity and hypothesis testing were carried out in this study. The normality test showed the value of Lcount < Ltable = 0.141 < 0.209 which was declared to be normally distributed. Homogeneity test shows the value of Fcount < Ftable = 1.281 < 1.523, then the data is declared homogeneous and feasible for further testing. Finally, the hypothesis test was carried out and showed the results of tcount = 3.618 and ttable = 2.101, namely tcount > ttable, indicating that this assumption is accepted. The mean value of the pretest in the experimental class is 58.3 and the control class is 56.7. After applying Kahoot! the pretest score in the experimental class got an average of 80.3 and the control class got an average of 74.2. From the results of this study it is evident that the application of the educational game Kahoot! can improve the learning outcomes of class X TKRO students at SMK Negeri 1 West Sumatra in the subject of Basic Automotive Technology.